Serum Procalcitonin and Presepsin Levels in Patients with Generalized Pustular Psoriasis - Nagai, Makoto; Imai, Yasutomo; Wada, Yoshihiro; Kusakabe, Minori; Yamanishi, Kiyofumi (Disease Markers, 2018)
Patients with generalized pustular psoriasis (GPP) often present with symptoms that must be differentiated from sepsis. Procalcitonin (PCT) and presepsin (P-SEP) are widely used as biomarkers for sepsis; therefore, we examined the serum PCT and P-SEP levels in patients with psoriatic diseases. The enrolled patients included 27 with psoriasis vulgaris (PV) (22 males, 5 females; mean age 47.7 years), 12 with psoriatic arthritis (PsA) (8 males, 4 females; mean age 51.3 years), and 15 with GPP (10 males, 5 females; mean age 63.7 years). The mean serum PCT levels in patients with PV, PsA, and GPP were 0.01 ng/mL (25th–75th percentile; 0.00–0.03), 0.013 ng/mL (0.00–0.03), and 0.12 ng/mL (0.05–0.18), respectively; the levels of PCT were higher for patients with GPP than with PV or PsA but were lower than the PCT cutoff value (0.5 ng/mL) for the diagnosis of infection. The mean serum P-SEP levels in patients with PV, PsA, and GPP were 144.9 pg/mL (25th–75th percentile; 78–181), 168.1 pg/mL (124–203), and 479.9 pg/mL (216–581), respectively. Unexpectedly, the levels of P-SEP in the patients with GPP were as high as the P-SEP cutoff value (317 to 647 pg/mL) used for the diagnosis of infection. We also found that neutrophils produced P-SEP, suggesting that the high serum P-SEP levels in patients with GPP might arise at least in part due to the P-SEP derived from neutrophils activated in GPP. Both serum PCT and P-SEP might therefore be useful as novel serum biomarkers for GPP because their levels were decreased by GPP treatments. However, the measurement of PCT might be more useful than the measurement of P-SEP for discriminating between GPP and sepsis.